# Solve for u 35=-7/3u 35=-73u
Rewrite the equation as -73u=35.
-73u=35
Multiply both sides of the equation by -37.
-37⋅(-73)⋅u=-37⋅35
Simplify both sides of the equation.
Simplify -37⋅(-73)⋅u.
Cancel the common factor of 3.
Move the leading negative in -37 into the numerator.
-37⋅(-73)⋅u=-37⋅35
Move the leading negative in -73 into the numerator.
-37⋅-73⋅u=-37⋅35
Factor 3 out of -3.
3(-1)7⋅-73⋅u=-37⋅35
Cancel the common factor.
3⋅-17⋅-73⋅u=-37⋅35
Rewrite the expression.
-17⋅-7⋅u=-37⋅35
-17⋅-7⋅u=-37⋅35
Cancel the common factor of 7.
Factor 7 out of -7.
-17⋅(7(-1))⋅u=-37⋅35
Cancel the common factor.
-17⋅(7⋅-1)⋅u=-37⋅35
Rewrite the expression.
-1⋅-1⋅u=-37⋅35
-1⋅-1⋅u=-37⋅35
Multiply.
Multiply -1 by -1.
1⋅u=-37⋅35
Multiply u by 1.
u=-37⋅35
u=-37⋅35
u=-37⋅35
Simplify -37⋅35.
Cancel the common factor of 7.
Move the leading negative in -37 into the numerator.
u=-37⋅35
Factor 7 out of 35.
u=-37⋅(7(5))
Cancel the common factor.
u=-37⋅(7⋅5)
Rewrite the expression.
u=-3⋅5
u=-3⋅5
Multiply -3 by 5.
u=-15
u=-15
u=-15
Solve for u 35=-7/3u

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top